The cost-effectiveness of cemiplimab plus chemotherapy as the first-line treatment for advanced non-small cell lung cancer - Lu, Tingting; Huang, Yufan; Cai, Zhongjie; Lin, Wangchun; Chen, Xiaoxiao; Chen, Ruijia; Hu, Yingying (Frontiers in Pharmacology, 2023)
Background: The EMPOWER-LUNG 3 clinical trial has shown that cemiplimab plus chemotherapy (CCT) significantly extended overall survival (OS) and progression-free survival (PFS) for patients with advanced non-small cell cancer (NSCLC) compared to placebo plus chemotherapy (PCT). However, the cost-effectiveness of this new treatment option remains unknown. Thus, we evaluated the cost-effectiveness of CCT versus (vs.) PCT as the first-line treatment for patients with advanced NSCLC from the perspective of the Chinese healthcare system. Methods: We constructed a Markov model to evaluate the cost-effectiveness of CCT as the first-line treatment for patients with advanced NSCLC. The transition probabilities were extracted from the survival data of the EMPOWER-LUNG 3 trial. The drugs’ costs were referred from national tender prices, while other model input parameters were derived from the EMPOWER-LUNG 3 trial and published literature. The outcome parameters mainly included quality-adjusted life years (QALYs) and incremental cost-effectiveness ratios (ICERs). One-way sensitivity analysis and probabilistic sensitivity analysis were performed to evaluate the robustness of the model outcomes. Results: Compared to PCT, in the CCT regimen, an additional $79,667 was spent in terms of the total cost and with an additional 0.31 QALYs, resulting in an ICER value of $253,148/QALY. Sensitivity analysis indicated that the hazard ratio (HR) of OS, the cost of cemiplimab (100 mg), and the HR of PFS, all significantly impacted the model’s results. The probability of CCT (vs. PCT) being cost-effective was 0% at a willingness-to-pay threshold of $38,201/QALYs in China. The scenario analysis showed that when the price of cemiplimab was reduced to less than $184.09/100 mg, the CCT regimen could be considered cost-effective as the first-line treatment for patients with advanced NSCLC compared to the PCT. Conclusion: In China, the CCT was not cost-effective as the first-line treatment for patients with advanced NSCLC.